Assessment of cognitive functions in middle-aged patients with type 2 diabetes - V.I. Velychko; V.L. Mykhailenko; Y.O. Tuliantseva; D.O. Lahoda; H.O. Danylchuk; Y.H. Tsyunchyk (Репродуктивная эндокринология, 2022)
Objectives: to evaluate cognitive functions in middle-aged patients with type 2 diabetes mellitus (T2DM). Materials and methods. The total number of participants was 72 people. The main group included 52 patients with T2DM (25 women, 27 men), the control group included 20 people (11 women, 9 men) without T2DM and without carbohydrate metabolism disorders. Cognitive function was assessed using the following scales: the Mini-Mental State Examination (MMSE) and the Montreal Cognitive Assessment (MoCA). Anxiety-depressive disorders were assessed using self-administered questionnaires: the Hospital Anxiety and Depression Scale (HADS) and the Beck’s Depression Inventory scale. Results. In the main group the average duration of T2DM was 8.31 ± 0.53 years, the average HbA1c level was 8.14 ± 0.07%, the fasting glycemia level was 7.07 ± 0.11 mmol/l, average body mass index (BMI) – 28.45 ± 0.60 kg/m2. 18 patients in this group had a normal body weight with an average BMI 23.58 ± 0.26 kg/m2, 12 people had an excessive body weight with an average BMI 28.21 ± 0.43 kg/m2, 22 patients had obesity of various severities with an average BMI 32.57 ± 0.51 kg/m2. The following results were obtained in patients with T2DM according to the MMSE scale: 54% (n = 28) of patients had no cognitive impairment (CI), 46% (n = 24) had various degrees of СІ, of which 27% (n = 14) had mild degree CI, 19% (n = 10) had moderate severity CI. According to the MoCA scale, cognitive deficit was found in 44% of the participants of the main group. According to the Beck’s scale, the following data were obtained: 10 (20%) people had no signs of depression, 34 (65%) of the respondents had signs of subclinical depression, 3 (15%) had signs of clinically expressed depression. Conclusions. We established a direct, close relationship between BMI and HbA1c level according to Spearman’s rank correlation coefficient (ρ = 0.730). When CI is detected, the doctor should review the treatment plan for such patients, avoiding complex management plans that overload patients physically, emotionally, or financially, and will not be implemented to the required extent due to cognitive deficits.